2019
DOI: 10.1080/21645515.2019.1614397
|View full text |Cite
|
Sign up to set email alerts
|

Responders and nonresponders to pharmacotherapy and allergen immunotherapy

Abstract: Allergen immunotherapy (AIT) is a very useful therapy for allergic rhinitis. However, some patients do not achieve the expected results. The aim of the study was to investigate the potential factors that could affect the result, either good or poor, from AIT. Methods: A retrospective analysis of 1624 patients with allergic rhinitis who underwent AIT and 1519 matched patients who underwent only symptomatic therapy (without AIT) was performed. Symptoms, medications scores and quality of life related to allergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Allergen immunotherapy is a long-term therapeutic process and can cause some side effects; therefore qualification for this treatment should be considered very carefully [18,19]. The new treatment strategies for SCIT require identification of factors predicting better effectiveness of this treatment [20,21]. The efficacy of SCIT has been confirmed by numerous clinical trials and a meta-analysis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Allergen immunotherapy is a long-term therapeutic process and can cause some side effects; therefore qualification for this treatment should be considered very carefully [18,19]. The new treatment strategies for SCIT require identification of factors predicting better effectiveness of this treatment [20,21]. The efficacy of SCIT has been confirmed by numerous clinical trials and a meta-analysis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Jakalski et al retrospective analysis of 1624 patients with AR found that AIT was less likely to be effective in polysensitized individuals and in those with a prolonged duration of AR prior to treatment initiation. 29 Similarly, Qi et al classified 284 patients having received subcutaneous AIT for HDM-induced AR as responders or non-responders. 30 The researchers found that a better response was associated with a short duration of allergy, a higher baseline symptom score, and local reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic failure can be considered as resulting from either inadequate clinical response or intolerable side effects. 14,15 The possible reasons for inadequate clinical response are summarized in Table 1. The current published guidelines and the medical literature (Pubmed, Cochrane Library, National Institute of Health, and Care Excellence) have been reviewed to look for guidance as to appropriate management when therapeutic failure arises.…”
Section: Discussionmentioning
confidence: 99%
“…We have considered therapeutic failure as either inadequate symptomatic response or intolerable side effects, which are both well recognized. 14,15 This is a series of 4 cases (3 therapeutic failure and 1 early relapse) encountered in our AIT clinic, where patients are treated using either SCIT or SLIT protocols, depending on clinical evaluation and patient preference. All patients provided informed consent to be included.…”
Section: Introductionmentioning
confidence: 99%